2021
DOI: 10.3390/jpm11111231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Predictive Role of Blood-Based Biomarkers in the Context of Suspicious Prostate MRI in Patients Undergoing Prostate Biopsy

Abstract: The aim of this study was to assess the predictive value of pre-biopsy blood-based markers in patients undergoing a fusion biopsy for suspicious prostate magnetic resonance imaging (MRI). We identified 365 consecutive patients who underwent MRI-targeted and systematic prostate biopsy for an MRI scored Prostate Imaging–Reporting and Data System Version (PI-RADS) ≥ 3. We evaluated the neutrophil/lymphocyte ratio (NLR), derived neutrophil/lymphocyte ratio (dNLR), platelet/lymphocyte ratio (PLR), systemic immune i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, some studies have also shown the limitations of MLR. A retrospective study by Pawel et al (Rajwa et al, 2021) concluded that MLR was not useful in the diagnosis of PCa. Racial differences in the association between MLR and PCa may also exist, as shown in a racially diverse study with a longer follow-up (Rundle et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have also shown the limitations of MLR. A retrospective study by Pawel et al (Rajwa et al, 2021) concluded that MLR was not useful in the diagnosis of PCa. Racial differences in the association between MLR and PCa may also exist, as shown in a racially diverse study with a longer follow-up (Rundle et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms combining PI-RADS score, age, and PSAD were also developed for csPCa prediction in patients with non-suspicious or equivocal mpMRI result (i.e., PI-RADS score ≤3) [ 27 ]. The predictive performance of the combination of other biomarkers has also been studied [ 28 ]. PHI and PHID were also attempted to further classify patients with positive mpMRI results [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although in a preprostatectomy setting, the SII has not been confirmed as a predictor of unfavourable biopsy outcomes [ 35 ], recently the SII has been extensively validated in patients who have already undergone radical treatment. Similarly to other haematological markers, the SII can be easily retrieved and calculated from a full blood count, which is an obligatory part of preoperative laboratory evaluations.…”
Section: Discussionmentioning
confidence: 99%